HVSR Microtremor Analysis to Assess Subsurface Fault Characteristics and Geothermal Potential in Kepahiang - Rabbani, Muhammad Rifqi; Hadi, Arif Ismul; Harlianto, Budi; Farid, Muchammad; Raihana, Hana; Anggi, Arya Putra (JURNAL GEOCELEBES, 2025)
Kepahiang, Bengkulu, is an area with considerable geothermal potential, especially in the Air Sempiang and Babakan Bogor areas. This study aims to analyze subsurface fault characteristics and assess geothermal potential using the Horizontal-to-Vertical Spectral Ratio (HVSR) microtremor method. This passive seismic method is used to determine key geophysical parameters, including dominant frequency (f0), amplification factor (A0), shear wave velocity (vs), and primary wave velocity (vp), which are essential for characterizing subsurface geological structures and identifying geothermal reservoir zones. The results show that dominant frequency values in Kepahiang range from 1.24 Hz to 20.45 Hz, while the amplification factor varies between 1.29 and 7.22. vs values range from 121.61 m/s to 3251.79 m/s, and vp values range from 214.91 m/s to 6469.79 m/s. These findings suggest that the surface layer consists mainly of alluvium and hard sandy gravel, with thicknesses varying between 10 and 50 meters. The 3D subsurface model constructed from the data indicates the presence of fault-controlled geothermal manifestations, mainly influenced by the Babakan Bogor Fault and Bogor Fault. These faults facilitate the upward migration of geothermal fluids, forming surface manifestations such as hot springs, fumaroles, and altered rocks. The geothermal system in the study area is classified as a low-temperature geothermal system, mainly caused by residual magmatic heat from Kaba Mountain and Bukit Hitam Crater. This research provides important insights for geothermal energy exploration and geotourism development in Kepahiang. These findings serve as a scientific basis for future geothermal resource assessment, land use planning, and sustainable energy utilization.